Association between obesity and liver enzyme levels: a cross-sectional observational study among individuals visiting a diagnostic laboratory in Burdwan, West Bengal - Dan, Subhasish; Banerjee, Prithwijit; Dan, Satrajit; Sadhukhan, Sanjoy K. (International Journal Of Community Medicine And Public Health, 2025)
Background: Obesity is a global health crisis, acting as a risk factor for various chronic diseases. Elevated levels of liver enzymes are important biomarkers of liver disease and may signal metabolic changes resulting from obesity. The aim of this study was to explore the association between obesity and liver enzyme levels, while also assessing the role of sociodemographic, behavioural, and dietary factors in obesity prevalence. Methods: This was a cross-sectional observational study carried out among 390 individuals aged 18 to 59 years without any diagnosis of liver disease. Information regarding sociodemographic, behavioural, and dietary habits were collected using structured questionnaires. Anthropometric measures, blood pressure, fasting blood glucose, lipid profile, and liver enzyme levels were assessed using standard methods. Chi-square tests, t-tests, Pearson correlation, and univariate logistic regression were performed to evaluate the relationships between variables. Results: Obesity prevalence among the study participants was 67.2% and a statistically significant relationship was found between obesity and elevated liver enzyme levels (p<0.05). No significant associations were found between obesity and sociodemographic or behavioural variables, but excess oil and sugar consumption were linked to obesity. Furthermore, logistic regression analysis revealed that sugar consumption, high systolic blood pressure, fasting plasma glucose, and liver enzyme levels were significantly associated with obesity. Conclusion: A significant association was identified between obesity and elevated levels of liver enzymes, indicating that they could be used as non-invasive biomarkers for detecting liver disease in early stages among overweight and obese individuals.